2023
DOI: 10.1038/s41467-023-43718-w
|View full text |Cite
|
Sign up to set email alerts
|

Design and structural validation of peptide–drug conjugate ligands of the kappa-opioid receptor

Edin Muratspahić,
Kristine Deibler,
Jianming Han
et al.

Abstract: Despite the increasing number of GPCR structures and recent advances in peptide design, the development of efficient technologies allowing rational design of high-affinity peptide ligands for single GPCRs remains an unmet challenge. Here, we develop a computational approach for designing conjugates of lariat-shaped macrocyclized peptides and a small molecule opioid ligand. We demonstrate its feasibility by discovering chemical scaffolds for the kappa-opioid receptor (KOR) with desired pharmacological activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Recently, PDCs have been designed to target the KOR to generate compounds with high receptor specificity, while also reducing analgesic side effects. 136 In this study, the crystal structure of KOR complexed with a ligand, MP1104, 137 was used to computationally design a series of PDCs that link KOR ligands based on MP1104 to thioether cyclized peptides designed to interact with the extracellular loops of KOR. Before small-molecule conjugation, the computationally designed peptides were assessed in cell-based assays which demonstrated that the compounds were unable to displace an orthosteric ligand at concentrations as high as 10 μM.…”
Section: Peptide−drug Conjugates For Cns Targets Peptide−drug Conjuga...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, PDCs have been designed to target the KOR to generate compounds with high receptor specificity, while also reducing analgesic side effects. 136 In this study, the crystal structure of KOR complexed with a ligand, MP1104, 137 was used to computationally design a series of PDCs that link KOR ligands based on MP1104 to thioether cyclized peptides designed to interact with the extracellular loops of KOR. Before small-molecule conjugation, the computationally designed peptides were assessed in cell-based assays which demonstrated that the compounds were unable to displace an orthosteric ligand at concentrations as high as 10 μM.…”
Section: Peptide−drug Conjugates For Cns Targets Peptide−drug Conjuga...mentioning
confidence: 99%
“…Recently, PDCs have been designed to target the KOR to generate compounds with high receptor specificity, while also reducing analgesic side effects . In this study, the crystal structure of KOR complexed with a ligand, MP1104, was used to computationally design a series of PDCs that link KOR ligands based on MP1104 to thioether cyclized peptides designed to interact with the extracellular loops of KOR.…”
Section: Peptide–drug Conjugates For Cns Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the agonist-bound structures, six are bound with small molecules MP1104 (PDB ID: 6B73) [ 54 ], nalfurafine (PDB ID: 7YIT) [ 38 ], GR89696 (PDB ID: 8DZR, 8DZS) [ 55 ], and momSalB (PDB ID: 8DZP, 8DZQ) [ 55 ]. The remaining three are bound with short peptides dynorphin (PDB ID: 7Y1F, 8F7W) and de novo cyclic peptide(DNCP)-β-naloxamine (NalA) (PDB ID: 8FEG) [ 56 , 57 , 58 ]. X-ray diffraction methods were employed in determining two antagonist-bound [ 52 , 53 ] and two agonist-bound structures [ 38 , 54 ].…”
Section: Structural Overview Of Kormentioning
confidence: 99%
“…Dysregulation of circadian rhythm has been associated with various health conditions, including metabolic disorders, cardiovascular diseases, and certain cancers 19 21 . Recent studies highlighted their role in neurological disorders such as cognitive diseases 22 . Although REV-ERBs share similar molecular domain organization to most nuclear hormone receptors, they are distinctive because they lack the carboxy-terminal helix-12 activation function 2 (AF-2) region.…”
Section: Introductionmentioning
confidence: 99%